The impact of a professional development program on english language teachers’ classroom performance (2014)
This article reports the findings of an action research study on a professional development program and its impact on the classroom performance of in-service English teachers who worked at a language institute of a Colombian state university. Questionnaires, semi-structured interviews, class observations, and a researcher’s journal were used as data collection instruments. Findings suggest that these in-service teachers improved their classroom performance as their teaching became more communicative, organized, attentive to students’ needs, and principled. In addition, theory, practice, reflection, and the role of the tutor combined effectively to help the in-service teachers improve classroom performance. It was concluded that these programs must be based on teachers’ philosophies and needs and effectively articulate theory, practice, experience, and reflection.En este artículo se presentan los resultados de una investigación-acción en un programa de desarrollo profesional y su impacto en el desempeño de clase de profesores de inglés de un instituto de lenguas de una universidad pública colombiana. Para recoger los datos se utilizaron cuestionarios, entrevistas, observaciones de clase y el diario del investigador. Los resultados sugieren mejorías en el desempeño de los docentes, ya que la enseñanza fue más comunicativa, organizada, atenta a las necesidades de los estudiantes y basada en principios. La teoría, la práctica, la reflexión y el papel desempeñado por el tutor se combinaron de manera efectiva para ayudar a los profesores a mejorar. Se concluye que los programas de desarrollo profesional deben planearse con base en las filosofías y necesidades de los profesores y articular la teoría, la práctica, la experiencia y la reflexión de manera más efectiva.